Analisis Tingkat Pemahaman Belajar Matematika Siswa Sekolah Luar Biasa (SLB) Berdasarkan Tinjauan Neuroscience - Nugroho, Alexander Febrian; Binuryan, Podang; Rudhito, Marcellinus Andy (Supermat : Jurnal Pendidikan Matematika, 2024)
This problem began with researchers' curiosity regarding the level of understanding of mathematics learning among mentally retarded students at SLB Marganingsih in terms of neuroscience. The aim of this research is to find out how mentally retarded students at SLB Marganingsih use a neuroscience approach. The type of research used in this research is a qualitative research method. Qualitative research methods will be used in this research to understand the experiences, perceptions, and understanding of SLB students in depth. This research was carried out at SLB Marganingsih, with the research subjects being six students in a class with intellectual disabilities. The variable in this research is the level of understanding of students in classes with intellectual disabilities at SLB Marganingsih in learning mathematics. The results of observational research on six children (NM, WN, AN, AR, AL, and ST), taking into account seven neuroscientific aspect factors, showed significant differences. The processing of mathematical information is different for each child, such as good mathematical understanding in NM, difficulty applying it in WN, and the need for a cheerful approach in AN. Brain limitations also play a role, such as limited memory in the left brain of WN, passive tendencies and difficulty adapting in AR, and childish characteristics in ST. Parental and teacher assistance, a learning environment, and various interactive learning methods are essential. Types of brain plasticity that continue to develop, as well as different IQ groups